Classification of Arcs in Finite Projective Plane of Order Sixteen - Najm A. Al-Seraji; Riyam A. Al-Ogali (Al-Mustansiriyah Journal of Science, 2018)
The aim of the paper is to classify certain geometric structures, called arcs. The main computing tool is the mathematical programming language GAP. In the plane PG(2,16),the important arcs are called complete and are those that cannot be increased to a larger arc. So far, all arcs up to size eighteen have been classified. Each of these arcs gives rise to an error-correcting code that corrects the maximum possible number of errors for its length.